(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper we have considered diverse distribution to acquire the system reliability of a n-course system. The assessment of reliability is considered primarily for course systems. For this reason, a few distributions are considered specifically, exponential, Weibull, gamma, Rayleigh, Lindley, uniform and two-point distribution. At that point some notable distributions in particular, exponential, gamma and Weibull distribution are utilized to assess the reliability of n - course system. The numerical values R(1), R(2), R(3) and R3 have likewise been processed and given in unthinkable structures to some particular values of the parameters.